IGBO APPRENTICESHIP MODEL AND MENTORSHIP IN THE NIGERIAN UNIVERSITY SYSTEM: A COMPARATIVE ANALYSIS - Omeire, Charles Obioma (African Journal of Social and Behavioural Sciences, 2025)
There is a growing concern among Igbo people that the apprenticeship system, which produced a lot of their prominent sons, is on the decline. Similarly, in the Nigerian university system, there appears to be appreciable decline in mentoring. The study examined the Igbo apprenticeship model, its structure, and modus operandi, and compared it to mentorship in Nigerian universities. Kram’s mentoring theory provided the theoretical foundation for the study, which is essentially qualitative. The data utilized were obtained from secondary sources, largely text books and journals. The study maintained that mentorship is critical for capacity building and beneficial to mentees, mentors, the university and society. It reiterated the vitality, value and relevance of the Igbo apprenticeship model in addressing contemporary problems of insecurity and unemployment in Nigeria. Consequently, the study recommended, among other things, that the Igbo apprenticeship model be revamped and that the other socio-cultural groups in Nigeria be encouraged to domesticate or adapt same in their zones. It further recommended that the mentorship process in Nigerian universities be structured and integrated as part of the promotion requirements for junior academic and administrative staff.